Diagnostic accuracy of aldosterone and renin measurement by chemiluminescent immunoassay and radioimmunoassay in primary aldosteronism. Issue 5 (May 2016) - Burrello, Jacopo; Monticone, Silvia; Buffolo, Fabrizio; Lucchiari, Manuela; Tetti, Martina; Rabbia, Franco; Mengozzi, Giulio; Williams, Tracy A.; Veglio, Franco; Mulatero, Paolo
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Up to 50% of hypertensive patients should be screened for primary aldosteronism, using the aldosterone to renin (or plasma renin activity) ratio [aldosterone to active renin ratio (AARR) and aldosterone to plasma renin activity ratio (ARR), respectively]. Aim of the study was to prospectively compare the diagnostic accuracy of AARR (measured by chemiluminescent immunoassay) and ARR (measured by radioimmunoassay) as screening tests for primary aldosteronism and aldosterone assays (measured by chemiluminescence and radioimmunoassay) during confirmatory testing. Methods: One hundred patients were screened for primary aldosteronism and 34 underwent confirmatory testing. The cut-offs for ARR and AARR were 30 ng/dl/ng/ml/h and 3.7 ng/dl/mU/l, respectively. Patients with positive confirmatory test underwent subtype diagnosis. Results: Seventy-five patients were essential hypertensive patients, 15 had idiopathic hyperaldosteronism, five aldosterone-producing adenoma (APA) and five with undefined diagnosis. The AARR displayed a sensitivity of 90% and a specificity of 99%, the ARR had a sensitivity of 100% and a specificity of 73%. Of the two of 20 primary aldosteronism patients missed by AARR, none resulted affected by APA. All primary aldosteronism patients were correctly diagnosed by chemiluminescence at confirmatory testing. In the total sample of 168 measurements both the correlation for plasma renin activity with renin and for aldosterone in chemiluminescence and radioimmunoassay were highly significant (ρ = 0.70, P  < 0.001 and ρ = 0.78, P  < 0.001, respectively). On receiver operator characteristics curves, the area under the curve for AARR was 0.989 [95% confidence interval (CI) 0.97–1] and 0.934 for ARR (95% CI 0.89–0.98), which were not significantly different. Conclusion: The automated aldosterone and renin chemiluminescent assay is a reliable alternative to the radioimmunometric method, especially for APA detection.